Enzymatic hydrolysis of eucalyptus biomass for bioethanol production: a bibliometric analysis (Research, Society and Development, 2018)
The energy matrix in the Brazilian and world scenarios has undergone significant changes during the last decades. Due to oscillations in the price of the oil barrel and its derivatives, the study of alternative energies has been intensifying. In this context, the production of second generation bioethanol has been considered as a way to meet this demand. Besides being able to partially solve the dependence of the use of fossil fuels, this technology stands out for utilizing lignocellulosic industries residues, adding value to this material. This article consists of a bibliometric review of this application, giving an overview of the advances made to date. A quantitative analysis of the articles found in the Web of Science database was carried out, followed by a qualitative analysis. Subsequently, the convergences and divergences between the articles were identified. The results demonstrate that some improvements are still needed in the process, however the technique is feasible and advantageous in the production of bioethanol.